Vegetation diversity and structure of urban parks in Cilegon City, Indonesia, and local residents’ perception of its function - MUHLISIN MUHLISIN; JOHAN ISKANDAR; BUDHI GUNAWAN; MARTHA FANI CAHYANDITO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Muhlisin, Iskandar J, Gunawan B, Cahyandito MF. 2021. Vegetation diversity and structure of urban parks in Cilegon City, Indonesia, and local residents’ perception of its function. Biodiversitas 22: 2589-2603. The existence of urban parks is very essential for cities because they provide ecosystem services and benefits to humans. Diversity and structure of vegetation in urban parks play significant role in delivering several functions of ecosystem services. This paper aims to explore and analyze the vegetation diversity and structure, as well as ecosystem services of eight urban parks in Cilegon City, Banten Province, Indonesia. Vegetation analysis and residents’ perception are also conducted in this research. The analysis of vegetation is focused on horizontal structure of vegetation, including plant diversity, plant habitus, the original distribution of the plants, and vertical structure of vegetation (canopy stratification and vegetation profile). The residents’ perceptions are collected using interviews of selected respondents. The identification of vegetation recorded 114 plant species from 46 families are found in the concerned urban parks, however, the diversity and species richness in these parks tended to be low. The vegetation communities are uncertain and dominated primarily by non-native and invasive species. The canopy stratification is relatively homogeneous with the dominant plants having less than one meter in height, such as Ruellia simplex and Syzygium paniculatum. The vegetation planted in the urban parks are mostly ornamental plants that provide much more aesthetic function rather than ecological purpose, daily human needs, or other ecosystem services. This fact shows that urban parks in the study area have only few ecosystem services, hence they need some improvements in order to have more environmental services and to be able to enjoy more by the community.